Analisis Yuridis terhadap Pembatalan Keputusan Tata Usaha Negara oleh PTUN: Menelaah Alasan Hukum yang Digunakan Hakim Dalam Membatalkan KTUN - Tansya Hadiansyah Ramdi; Intan Sukmawati; Euis Maesaroh; Aji Nugraha; Taufiq Alamsyah (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2026)
This study aims to gain an in-depth understanding of the legal reasoning used by judges in the Administrative Court (PTUN) in annulling State Administrative Decisions (KTUN), as well as to examine the legal implications for the parties involved and the overall system of government administration. This research employs a normative juridical method with three approaches: statutory, conceptual, and case approaches. The analysis was conducted qualitatively by studying reference books and reviewing court decisions. The study shows that the annulment of KTUN by PTUN judges is based on three important factors, namely lack of authority (ultra vires), procedural defects, and substantive defects in the decision. In addition, violations of the General Principles of Good Governance (AUPB), such as the principles of legal certainty, prudence, and proportionality, also constitute important considerations for judges. In the judicial process, judges not only consider the formal aspects of the law, but also take into account substantive justice in order to protect citizens’ rights from improper governmental actions. The implications of the annulment of KTUN include the restoration of the plaintiff’s rights through the process of restitutio in integrum, the obligation of administrative officials to revoke or correct the issued decision, as well as the potential impact on third parties involved in the decision. In general, the annulment of KTUN serves as a legal control mechanism over government administration while also encouraging the realization of good and transparent governance within a state governed by the rule of law.